ANALISIS DAYA SERAP DUNIA KERJA TERHADAP ALUMNI SMK NEGERI 1 TUKAK SADAI TAHUN 2014 - 2020 - Sutiono Tjasim Sukarjo; Dede Tarmana (STKIP ROKANIA, 2021)
This study aims to determine the description of the data regarding the alumni of SMK Negeri 1 Tukak Sadai based on the profession of work and to determine the absorption capacity of the world of work. To achieve the predetermined research objectives, the researchers processed the data using proportional methods and descriptive statistical methods. The data used in this study is secondary data about the alumni of SMK Negeri 1 Tukak Sadai period 2014-2020. The data source was obtained directly from the database of SMK Negeri 1 Tukak Sadai, where the school routinely collects data on its graduates. The results showed that the average percentage of the alumi professions who worked was 48%, which is the highest percentage compared to the average of other professions and the lowest average value of professions is the entrepreneurial profession with an average value of 2%. The profession that can reduce unemployment and increase the absorption of the world of work is the entrepreneurial profession. The absorption of the world of work for the alumni of SMK Negeri 1 Tukak Sadai is still below 50%, so that the absorption of the world of work has not been maximal. Key words: work field absorption, entrepreneurial, work profession.